An Assessment of Power Sources for Improved Energy Supply in University of Maiduguri - Muhammad M. HAMIDU; Abubakar M. EL-JUMMAH; Muhammad SHUWA (FUDMA Journal of Engineering and Technology, 2025)
University of Maiduguri makes use of Electricity supply from the National grid and diesel powered generators along site solar supply. This assessment was prompted by disruptions in electricity supply, exacerbated by rising diesel prices and commercialized electricity tariffs. The study aims to evaluate the impact of electricity costs and reasons behind the choice of alternative power sources for the University, focusing on the comparative costs over a projected ten-year period. In order to effectively carry out the assessment, this work compares the design of the combined analysis of solar and diesel power plants to the national grid commercial supply. A methodological approach was adopted, combining quantitative data analysis with interviews to gather insights. Data was analyzed using Excel for forecast projections. The findings indicate that over ten years, the total projected costs for electricity supply are ₦90.82 billion for the national grid, ₦34.02 billion for diesel generators, and ₦21.38 billion for solar energy. While electricity from the national grid incur the highest costs, the solar system offers the most economical solution. Interviews revealed that the high costs of energy are influenced not only by direct pricing from the national grid and diesel but also by consumer behavior. Increasing awareness and educating users about energy conservation could significantly alleviate energy expenses within the university. Given these findings, it is recommended to pursue a complete installation of solar power systems at the University of Maiduguri. Furthermore, investigating hybrid power solutions, such as combining solar with wind energy, is suggested for enhanced efficiency and effectiveness in electricity supply.
Keywords: Assessment, power sources, electricity supply, University of Maiduguri.